PI3K/Akt/mTOR Signaling Pathway: Role in Esophageal Squamous Cell Carcinoma, Regulatory Mechanisms and Opportunities for Targeted Therapy - Luo, Qian; Du, Ruijuan; Liu, Wenting; Huang, Guojing; Dong, Zigang; Li, Xiang (Frontiers in Oncology, 2022)
Esophageal squamous cell carcinoma (ESCC), is the most common type of esophageal cancer worldwide, mainly occurring in the Asian esophageal cancer belt, including northern China, Iran, and parts of Africa. Phosphatidlinositol 3-kinase (PI3K)/ protein kinase B (Akt)/ mammalian target of rapamycin (mTOR) signaling pathway is one of the most important cellular signaling pathways, which plays a crucial role in the regulation of cell growth, differentiation, migration, metabolism and proliferation. In addition, mutations in some molecules of PI3K/Akt /mTOR pathway are closely associated with survival and prognosis in ESCC patients. A large number of studies have found that there are many molecules in ESCC that can regulate the PI3K/Akt/mTOR pathway. Overexpression of these molecules often causes aberrant activation of PI3K/Akt/mTOR pathway. Currently, several effective PI3K/ Akt /mTOR pathway inhibitors have been developed, which can play anticancer roles either alone or in combination with other inhibitors. This review mainly introduces the general situation of ESCC, the composition and function of PI3K/Akt/mTOR pathway, and regulatory factors that interact with PI3K/Akt/mTOR signaling pathway. Meanwhile, mutations and inhibitors of PI3K/Akt/mTOR pathway in ESCC are also elucidated.